Altered diversity of bacterial communities in two Drosophila species under laboratory conditions and lead exposure - Beribaka, Mirjana B.; Dimkić, Ivica Z.; Jelić, Mihailo Đ.; Stanković, Slaviša M.; Pržulj, Novo M.; Anđelković, Marko Lj.; Stamenković-Radak, Marina M. (Archives of Biological Sciences, 2021)
Paper description: Changes in climatic and environmental parameters give relevance to the study of factors that shape the interactions between insects and microbiota, and to their adaptive significance. Microbiota diversity in two Drosophila species from field-collected samples and their laboratory progeny with and without exposure to lead pollution is the first investigation of the bacterial communities associated with subobscura. Significant species-specific differences in bacterial composition between populations and treatments was revealed. The diversity of bacterial communities increased in both species under lead exposure. Increased microbiota diversity under lead pollution could serve as an indicator of the adaptive response to environmental stress. Abstract: The composition of microbiota affects different traits of Drosophila throughout its life cycle and represents an important part of the adaptive response to environmental changes, such as increased levels of accumulated heavy metals in their habitats. We investigated the effects of lead added to the feeding substrate on the microbiota diversity in the fruit flies, Drosophila melanogaster and Drosophila subobscura. We compared the bacterial diversity of wild-caught flies and their progeny reared under standard laboratory conditions. We analyzed the shifts in bacterial diversity in the experimental groups of flies reared for 13 generations on standard and lead(II) acetate (Pb(CH3COO)2), Pb acetate-saturated substrates. Identification of the main bacterial genera was performed by next-generation sequencing (NGS) of the V3-V4 variable regions of the 16S rRNA gene. Results indicate significant species-specific differences in bacterial composition between natural and laboratory populations, and between the substrates. Diversity increased in both species under prolonged exposure to lead-polluted substrate, suggesting a potential adaptive response to an environmental stress.